2000
DOI: 10.1006/acha.2000.0310
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Approximation of the Free-Space Heat Kernel

Abstract: Abstract-Many problems in applied mathematics, physics, and engineering require the solution of the heat equation in unbounded domains. Integral equation methods are particularly appropriate in this setting for several reasons: they are unconditionally stable, they are insensitive to the complexity of the geometry, and they do not require the artificial truncation of the computational domain as do finite difference and finite element techniques. Methods of this type, however, have not become widespread due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 13 publications
0
89
0
1
Order By: Relevance
“…Discretization and evaluation of the single layer potential. We first consider the evaluation of the single layer potential, following the treatment of the heat equation in [31,35,53]. There are three fundamental observations to be made.…”
Section: Discretization and Numerical Evaluation Of Layer Potentialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Discretization and evaluation of the single layer potential. We first consider the evaluation of the single layer potential, following the treatment of the heat equation in [31,35,53]. There are three fundamental observations to be made.…”
Section: Discretization and Numerical Evaluation Of Layer Potentialsmentioning
confidence: 99%
“…Note that the integrand decays to zero exponentially fast when t − τ ≥ δ is bounded away from 0. In [31], it was shown that an efficient sum-of-exponentials approximation for the heat kernel exists in this case. Exactly the same idea can be applied here, with the result that N F ≈ 1/δ discrete Fourier modes are need to satisfy an estimate of the form…”
Section: Evaluation Of the History Partmentioning
confidence: 99%
See 3 more Smart Citations